Fragility of democratic minimalism: why the ballot is insufficient for democracy - Mace, Sam (Frontiers in Political Science, 2025)
This paper engages Hamid's democratic minimalism which proposes democracy via ballot form is not only necessary but sufficient for democracy to flourish. Hamid proposes a state sustaining democratic norms such as voting, free elections, and protection of civil society enlarging the ideological playing field creating different types of democratic states. However, this paper argues this argument fails to protect democracy. By narrowing the scope for procedural democracy to protect itself Hamid opens the door for authoritarianism to emerge democratically. The paper demonstrates this both theoretically and practically via a case study of Hungary. Focusing on the emergence of electoral authoritarianism and polarization, the paper argues procedural democracy cannot reliably retain its shape in a minimalist setting. Through a theoretical realist lens the paper highlights the limits of minimalism arguing democracy requires a thicker relationship to value via deliberation in order for a sustainable arrangement of democracy to emerge. The conclusion of the paper is that minimalism is too thin to sustain democracy creating the conditions for its ultimate demise as shown in the case study of Hungary.